Making It Work: Inuit Labour, Unionization, and Employment Partnerships in Nunavut’s Mining Economy - Slowey, Gabrielle (Études Inuit Studies, 2025)
This article examines Inuit participation in the labour force in Nunavut through a case study of the Mary River iron ore mine and the Qikiqtani Skills and Training for Employment Partnership (Q-STEP) program. Drawing on academic literature, policy documents, Inuit Impact and Benefit Agreements (IIBAs), union materials, and a one-day workshop, it explores the structural challenges Inuit workers continue to face, including housing shortages, educational inequities, language barriers, and distrust of southern institutions. The article argues that Inuit engagement with wage labour cannot be understood through simplistic binaries of exploitation versus empowerment. Instead, Inuit communities are navigating resource development in pragmatic and innovative ways that seek to balance economic opportunity, cultural continuity, and political self-determination. Attention is paid to Inuit-led initiatives such as Q-STEP, the Tuttarvik employment application, and the role of the International Union of Operating Engineers (IUOE) Local 793 in supporting workplace training, retention, and safer labour conditions. The paper contributes to scholarship on Indigenous labour and Arctic political economy by emphasizing Inuit agency and institutional innovation. It argues that Inuit participation in wage labour and traditional land-based practices is not mutually exclusive but increasingly interconnected within contemporary forms of Arctic development and governance.